Effects of Eucalyptus species plantations and crop land on selected soil properties - Bikila Mengistu; Fikru Amayu; Wondmagegn Bekele; Zerihun Dibaba (Geology, Ecology, and Landscapes, 2020)
The physical and chemical properties of soil are strongly influenced by type of land use system implemented. Eucalyptus is a group of tree species, which is native to Australia but widely grown throughout the world. In Ethiopia also due to its fast-growing nature of eucalyptus combined with its extensively recognized socio-economic benefits, this introduced species has been widely planted. Even if the economic contributions there are a lot of controversies are raised from different parts of the world. Therefore, this study is planned to evaluate the effects of Eucalyptus species plantations and crop land on selected soil properties around Bale. In the case ,moisture content, except for Goro district, for the other districts (Agarfa, Dello Menna, Goba, Robe) the amount of moisture content is higher in the soil under Eucalyptus plantation land uses than crop land. When we see the overall mean wise comparison of the whole land uses, as the depth increases the overall mean potential of soil chemical properties in PH, OC%, OM%, and available P decreases. But in the case of EC as the depth increases the concentration slightly increases. When we see the general overview of the land uses, no significant differences were observed between Eucalyptus plantation land uses and crop land use. Even in most of the parameter especially in soil organic carbon and soil organic matter the highest value were recorded in Eucalyptus plantation land uses than crop land use. This is due to the recycling of nutrient through decomposition of different tree parts. In terms of crop land due to cereal crop intensive agricultural system, most the soil nutrient is depleted. Therefore, this finding concluding that eucalyptus could positively impact soil physical and chemical properties through decayed litter than intensively cultivated crop land.